Eros, Thanatos and the Bridge: On the promises and perils being human (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
Guided by the metaphor of ‘building bridges’, this rhetorical, phenomenological study examines the nature of human connectivity and the unique challenges arising from the species-wide tendencies toward attraction and aversion, creation and destruction. Primarily drawing on psychoanalysis and Daseinsanalysis, it also incorporates perspectives from the natural sciences and Eastern contemplative traditions to integrate scientific, psychological and philosophical insights regarding the nature of human existence and human relationality. The study centres around a detailed phenomenological-hermeneutic analysis of the meaning of ‘building bridges’ and its significance for everyday life and the practice of psychotherapy. This analysis leads to further explication of the article’s primary concern with human existence and human relationality. The article concludes with descriptions of specific real-life examples that illustrate the consequences of both compassionate and aggressive behaviours. These examples underscore the need to find meaning, purpose, hope, and the courage to care in such turbulent times as we face today.
Keywords: Love; aggression; connection; human existence; freedom; Freud; Dasein; neuroscience; Eastern thought “Where danger lies; there also saving power.”